Tissue-resident memory T cells in chronic liver diseases: Phenotype, development and function - Li, Yikang; You, Zhengrui; Tang, Ruqi; Ma, Xiong (Frontiers in Immunology, 2022)
Tissue-resident memory (TRM) T cells are a unique subset of memory T cells that are critical for the first line of defense against pathogens or antigens in peripheral non-lymphoid tissues such as liver, gut, and skin. Generally, TRM cells are well adapted to the local environment in a tissue-specific manner and typically do not circulate but persist in tissues, distinguishing them from other memory T cell lineages. There is strong evidence that liver TRM cells provide a robust adaptive immune response to potential threats. Indeed, the potent effector function of hepatic TRM cells makes it essential for chronic liver diseases, including viral and parasite infection, autoimmune liver diseases (AILD), nonalcoholic fatty liver disease (NAFLD), hepatocellular carcinoma (HCC) and liver transplantation. Manipulation of hepatic TRM cells might provide novel promising strategies for precision immunotherapy of chronic liver diseases. Here, we provide insights into the phenotype of hepatic TRM cells through surface markers, transcriptional profiles and effector functions, discuss the development of hepatic TRM cells in terms of cellular origin and factors affecting their development, analyze the role of hepatic TRM cells in chronic liver diseases, as well as share our perspectives on the current status of hepatic TRM cell research.